AAOS Clinical Practice Guideline Summary: Management of Osteoarthritis of the Knee (Nonarthroplasty), Third Edition - Brophy, Robert H; Fillingham, Yale A (Journal of the American Academy of Orthopaedic Surgeons, 2022)
Management of Osteoarthritis of the Knee (nonarthroplasty) Evidence-Based Clinical Practice Guideline is based on a systematic review of published studies for the nonarthroplasty treatment of osteoarthritis of the knee in adults (ages 17 years and older). The purpose of this clinical practice guideline is to evaluate current best evidence associated with treatment. The scope of this guideline contains nonpharmacologic and pharmacologic interventions for symptomatic osteoarthritis of the knee, including surgical procedures less invasive than knee arthroplasty. It does not provide recommendations for patients with rheumatoid arthritis, arthritis of other joints, or other imflammatory athropathies. This guideline contains 29 recommendations to assist all qualified and appropriately trained healthcare professionals involved in the nonarthroplasty management of osteoarthritis of the knee and provide information for patients. In addition, the work group highlighted the need for better research into intra-articular corticosteroid, hyaluronic acid, and platelet-rich plasma detailing osteoarthritis characterization, including subgroup analyses and osteoarthrosis severity stratification, and clinically relevant outcomes with control subjects for bias and cost-effectiveness analysis. Studies comparing outcomes in patients with mild-to-moderate knee osteoarthritis and an MRI confirmed meniscal tear who have undergone partial meniscectomy after failing to improve with a course of conservative treatment (nonsteroidal anti-inflammatory drugs, steroid injection, and physical therapy) versus those who have undergone partial meniscectomy without a dedicated course of conservative treatment. Prospective randomized trials or prospective cohort studies are still needed to establish efficacy of individual oral nonsteroidal anti-inflammatory drugs within specific subgroups and populations to tailor systemic medications to help increase efficacy and decrease the risk of adverse effects.